Prolonged Detection of SARS-CoV-2 in a Patient With the Development of New Clinical Symptoms. Issue 2 (March 2021) - Awoniyi, Amaka; Rohm, Zachery; Paranjape, Neha; Arinze, Folasade
Abstract : Abstract: We present a case of a 65-year-old woman with a persistently positive nasopharyngeal swab for severe acute respiratory syndrome coronavirus 2 PCR who developed new complications of coronavirus disease 2019 (COVID-19) 63 days from illness onset. She presented with intermittent fevers, fluctuating disorientation, gait instability, diffuse corticospinal tract signs, and acute venous thromboembolism. No alternate diagnosis was identified. This case highlights the potential for prolonged SARS-CoV-2 PCR positivity and persistent multisystem complications (particularly neurological), even after several months of initial COVID-19 diagnosis.